Otolaryngologic management of Down syndrome patients: what is new?. Issue 6 (December 2017) - Bassett, Ethan C.; Musso, Mary F.
Abstract : Purpose of review: The management of children with Down syndrome as it pertains to the otolaryngologist continues to evolve. Obstructive sleep apnea (OSA) has dominated the recent literature, but other topics including hearing loss, swallowing, and perioperative considerations are also reported. Recent findings: The prevalence of OSA in children with Down syndrome ranges from 57 to 73% in certain cohorts, and, whereas adentonsillectomy can decrease Apnea–Hypopnea Index, up to 80% may have persistent OSA. Surgical techniques involving reduction of the base of tongue are effective for those who fail adenotonsillectomy, and it is expected that drug-induced sleep endoscopy may improve outcomes. New technology is also on the horizon that can assist with diagnosis and treatment including computational modelling and upper airway stimulation. Children with Down syndrome may not respond to medical management of eustachian tube dysfunction as well as normally developing children. In addition, there is a high prevalence of inner ear anomalies, increasing the risk for sensorineural hearing loss. Summary: Questions remain pertinent to the otolaryngologist regarding the ideal management of children with Down syndrome. Additional studies are necessary, to optimize understanding and treatment of this complex population, in particular as opportunities develop with technological advances.